Differences in Total Cholesterol Levels after Administration of Green Tea in Patients with Hypercholesterolemia - Weni Kurnia sari (Sean Institute, 2023)
Cholesterol is a component of fatty acids found in the blood. This substance is needed by the body for certain processes for survival. Among them to form hormones, cells and treat nerve cells. Hypercholesterolemia is excess fat in the blood. Hypercholesterolemia can be overcome by consuming herbal medicines (natural ingredients, such as medicinal plants including green tea. Green tea (Camellia sinensis) contains polyphenols in the form of catechins, especiallyepigallocatechin-3-gallate (EGCG). It is a biologically active ingredient that can inhibit the pathogenicity of several chronic diseases, especially in cardiovascular diseases which can play an important role in reducing blood cholesterol levels. This type of research is quasi experiment (Quasi experiment) by designPretest-Postest with Control Group ((Latuconsina, 2018). The implementation of this study was to measure total cholesterol levels taken before and after giving green tea for 2 weeks. The study was conducted on hypercholesterolemia sufferers in the city of Padang. The material used in this study was 3 grams of clean and good quality green tea.The results of statistical analysis using the T-test 2 mean Independent to see the effect of changes in total cholesterol levels on green tea administration in the treatment group and without green tea administration in the control group obtained statistical test results p value <0.05, there was a difference between changes in total cholesterol in the treatment group with the control. The conclusion of this study was that there was a significant difference in initial and final total cholesterol in the treatment group (p<0.05). There was a significant difference of initial and final total cholesterol in the control group (p<0.05). There was a significant difference in changes in total cholesterol between the treatment and control groups ((p<0.05).